M*A*S*H. Season three [videorecording (DVD)] - Gelbart, Larry (Twentieth Century Fox Home Entertainment, 2008)
Explores the day-to-day lives of the people who live and work at the Mobile Army Surgical Hospital (MASH) stationed three miles from the front during the Korean War.